Internet usage among pregnant women for seeking health information: A review article - Marzieh Javanmardi (Iranian Journal of Nursing and Midwifery Research, 2018)
Background: In recent years, the Internet has become one of the most popular sources of health information for users, and pregnant women are no exception. This study aimed to investigate Internet usage among pregnant women for achieving health information on the finding of related studies. Materials and Methods: This review study was conducted by searching databases such as IranMedex, Magiran, Scientific Information Database, Irandoc, PubMed, Science Direct, Cochrane, Google Scholar, and Scopus in December 2016. Restrictions were placed on publication to within 16 years and language of publication was restricted to English and Persian. Keywords used in the search included information-seeking behavior, information-seeking, information needs, access to information, pregnancy, and pregnant women. Results: This search resulted in 106 related publications and among them sixteen articles met inclusion criteria. This review showed that the use of the Internet by pregnant women was driven by information needs, ease, and speed of access and finding people with the same situation. Fetal development, symptoms, and complications of pregnancy, prenatal tests and nutrition, activities during pregnancy, and stages of delivery were the most often mentioned topics of interest. The benefits of internet use include reduced anxiety, personal support, creating an emotional connection and an increased confidence. Conclusions: Health providers must have sufficient ability for interpreting the achieved information from the Internet and should allocate efficient amount of time for discussing information-seeking manners with pregnant women. Furthermore, they must try to respond to the doubts of pregnant women and provide valid and reliable online educational resources.